Litterært feltarbejde: En brugsanvisning - Lind, Hans (Passage - Tidsskrift for litteratur og kritik, 2023)
Based on the author’s experience in doing fieldwork on three Danish creative writing schools – Testrup Højskole, Gladiatorskolen, and Forfatterskolen – this article shows how ethnographic methods can contribute to the study of literary use. Engaging in the ongoing discussions in literary studies on postcritique, the article argues that the movement’s interest in the multifarious social uses of literature should be matched, methodologically, with the researcher’s own willingness to leave the desk and study literature where it is being used.